1975
DOI: 10.1071/ch9750033
|View full text |Cite
|
Sign up to set email alerts
|

Metal complexes of 1,10-phenanthroline derivatives. IX. 5T2 ↔ 1A1 spin transitions in iron(II) complexes of 2-(1,10-phenanthrolin-2-yl)thiazole derivatives

Abstract: The preparation of the tridentate chelating agents 2-(1,10- phenanthrolin-2-yl)thiazole, 2-(1,10-phenanthrolin-2-yl)-4-(2- pyridyl)thiazole 2-(1,10-phenanthrolin-2-yl)thiazolidine and 2-(1,10- phenanthrolin-2-yl)benzothiazole is described. Data from the spectra of the bis-ligand nickel complexes indicate that the ligands all have field strengths in the iron(II) crossover region. The temperature dependence of the magnetism of the bis-ligand iron(II) complexes reveals that, except for the complexes of the pyridy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Following this strategy, 2-(2 H -tetrazol-5-yl)-1,10- phenanthroline is designed, which includes two basic SCO components, i.e., tetrazole and 1,10-phenanthroline. Similar tridentate ligands, such as oxadiazole, thiazole, imidazoline, pyrazole, or triazole attached with 1,10-phenanthroline, have been reported by Goodwin et al, but only simple SCO properties are observed in the corresponding isolated iron(II) complexes. Herein, we report the syntheses and characterizations of an extensive series of iron(II) complexes using 2-(2 H -tetrazol-5-yl)-1,10-phenanthroline and its alkyl-substituted derivatives as ligands.…”
Section: Introductionsupporting
confidence: 74%
“…Following this strategy, 2-(2 H -tetrazol-5-yl)-1,10- phenanthroline is designed, which includes two basic SCO components, i.e., tetrazole and 1,10-phenanthroline. Similar tridentate ligands, such as oxadiazole, thiazole, imidazoline, pyrazole, or triazole attached with 1,10-phenanthroline, have been reported by Goodwin et al, but only simple SCO properties are observed in the corresponding isolated iron(II) complexes. Herein, we report the syntheses and characterizations of an extensive series of iron(II) complexes using 2-(2 H -tetrazol-5-yl)-1,10-phenanthroline and its alkyl-substituted derivatives as ligands.…”
Section: Introductionsupporting
confidence: 74%
“…The synthesis of ligands L1, L2 and L5-L7 were reported in our previous paper, 57,58 meanwhile the ligand L9 was synthesized according to the literature. 62 Toluene was refluxed over sodium-benzophenone and distilled under nitrogen prior to use. Dichloromethane was distilled under nitrogen from CaH 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The organic compounds used as ligands L1, L2 and L5-L7 were efficiently synthesized according to our reported procedures 57, 58 while the ligand L9 was synthesized according to the literature. 62 Following literature procedures, compounds L3 and L4 used as ligands were obtained in acceptable yields (Scheme 1) 57 while ligand L8 58 was prepared in a better yield and ligand L10 62 in even better yield (Scheme 2). corresponding complexes C1-C10 (Scheme 3), which were isolated as stable green solids in high yields (about 76%).…”
Section: Synthesis and Characterization Of The Chromium Complexes C1-c10mentioning
confidence: 99%
“…Owing to the progress in heterocycle synthetic chemistry, numerous pincer-type ligands composed of pyridine and other nitrogen-containing heterocycles have been designed and synthesized (Chart ). Some mononuclear Fe II and Co II complex families from these ligands, such as tpy and its derivatives, phenthiazole, phentetrazol, Schiff base ter-imines, , (2-thia) 2 py, , (4-thia) 2 py, (2-thia)­py 2 , 1-bpp, ,, 3-bpp, and trim were proven to be SCO-active.…”
Section: Introductionmentioning
confidence: 99%